Effects of acute supplementation of caffeine on cardiorespiratory responses during endurance running in a hot and humid climate - Wong, Fadzel Chee Ping; Chen, Chee Keong; Amit Bandyopadhyay (Indian Council of Medical Research, 2010)
BACKGROUND & OBJECTIVES: Athletes in Malaysia need to perform in a hot and humid climate. Chronic supplementation of caffeine on endurance performance have been studied extensively in different populations. However, concurrent research on the effects of acute supplementation of caffeine on cardiorespiratory responses during endurance exercise in the Malaysian context especially in a hot and humid environment is unavailable.